13m+6n-3m+8n=

Simple and best practice solution for 13m+6n-3m+8n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13m+6n-3m+8n= equation:


Simplifying
13m + 6n + -3m + 8n = 0

Reorder the terms:
13m + -3m + 6n + 8n = 0

Combine like terms: 13m + -3m = 10m
10m + 6n + 8n = 0

Combine like terms: 6n + 8n = 14n
10m + 14n = 0

Solving
10m + 14n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-14n' to each side of the equation.
10m + 14n + -14n = 0 + -14n

Combine like terms: 14n + -14n = 0
10m + 0 = 0 + -14n
10m = 0 + -14n
Remove the zero:
10m = -14n

Divide each side by '10'.
m = -1.4n

Simplifying
m = -1.4n

See similar equations:

| -10-5v-7v=6-8v | | x+4+3=4x+1 | | x^2+54x+679=0 | | 60=-4(-9+x) | | -200=4(6n-2) | | (8.5x)(2.25x)=3000 | | 8x+16=360 | | 25+6x=9x | | 2x+x=3000 | | 60=-4x-9+x | | -3x-4+6=2x+6+3x | | 8(3n+6)-20n-40= | | 2m=2[3(3+2m)-(3-m)] | | 7+3k=5k-3 | | 2(3x-4)=-(8-6x) | | -4a+5(-3a-3)=99 | | 7x^2-24x-21=-5 | | -9h-6+12h+40=12h | | Log[2](5x-3)=3 | | 2(-4-5p)+2p=-8(6p-5)+10(2+4p) | | 78=-7w+-13 | | 20p+7-11-p=-2(2p+4)-3(2p-2) | | 5ab=(b-1)*(4a+3) | | 6-2(x+4)=32 | | 4y^2-5y-30=0 | | 0.003x+1.2=0.15 | | 5.2+1.9x=2.9x | | 4x+17=112 | | 6(-3r+5)-5=115 | | 30x+x^2=10800 | | 20p+7-11-p=-2(2p+4) | | 5c+7a=116 |

Equations solver categories